Challenges in internationalisation for VietNam sme - Đinh, Nguyễn Bích Lê (2020)
Small and Medium Enterprises (SMEs) of Vietnam play an important role in the country's industrialization and modernization. There is a plenty of reasons why small and medium business should go international, for example bigger markets leading to bigger profits, cheaper supplies leading to more effective production process. The purpose of this study is to point out obstacles faced by SMEs in international activities and recommend strategy changes to answer the question: “How can SMEs in Vietnam achieve effectiveness when engaging in internationalization?”